ANALISIS MCDONALDISASI BENTUK PELAYANAN PUBLIK PADA SISTEM E-FILING DIREKTORAT JENDERAL PAJAK (DJP) ONLINE - Putri Maulina (Jurnal Public Policy, 2018)
In this contemporary era, the forms of public service in Indonesia have become increasingly practical and instant. Conditions like this to illustrate how the phenomenon of McDonaldization began to plague into public service systems, one of which is with the public service system e-Filing DJP Online. E-Filing DJP Online is an application of public services based on information and communication technology implemented by the state tax execution agency to provide easy access to services for the Taxpayers in Indonesia. The purpose of this study is to see how the principles of McDonaldization are applied in the public service system of tax agencies through the DGT Online e-Filing system. The theory approach used is McDonaldization Theory by George Ritzer, and the concept of Public Service. The method used is qualitative descriptive, with literature review approach. The results show that the DGT Online e-Filing system applies the principles of McDonaldization in the form of its services, namely: efficiency, quantified and qualified services, predictability, control, and ultimately the rationale for irrationality of service.Keywords: McDonaldization, Public Service, Tax, e-Filing